Tax-based Own Resources to Finance the EU Budget - Margit Schratzenstaller; Alexander Krenek (Intereconomics, 2019)
In the current negotiations about the European Union's next medium-term Multiannual Financial Framework (MFF) for the period 2021 to 2027, the system of own resources financing EU expenditures plays a relatively important role.
Keywords: 330